Situational Leadership, Work Culture, and Intrinsic Motivation towards Employee Performance PT. PLN (Perusahaan Listrik Negara) Persero Labuhan Batu Regency Area - Mhd. Husaini Annasri Lubis; Siti Lam'ah Nasution; Abd. Halim (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze situational leadership, work culture, and intrinsic motivation on employee performance at PT PLN (State Electricity Company) Persero Area Labuhanbatu Regency. This research uses quantitative methods, with analytical toolsSoftware IBM SPSS 25. The analysis techniques used include classical assumption test, multiple linear regression, hypothesis testing, and coefficient of determination. The results of the t test in this study indicate that the value oftcount situational leadership variable (X1) 4,09 > ttable1.68 with a significant value of 0.000 < from a probability value of 0.05 so it can be concluded that the situational leadership variable has a positive and significant effect on employee performance. Marktcount work culture variable (X2) 3.07 > ttable1.68 with a significant value of 0.004 < from a probability value of 0.05 so it can be concluded that the work culture variable has a positive and significant effect on employee performance. Marktcount intrinsic motivation variable (X3) 6.26 > ttable1.68 with a significant value of 0.000 < from a probability value of 0.05 so it can be concluded that the intrinsic motivation variable has a positive and significant effect on employee performance.Simultaneously, the variables of situational leadership, work culture, and intrinsic motivation have a positive and significant influence on employee performance. This means that the hypothesis in this study is accepted, as evidenced by the value of Fcount > Ftable (25.19 > 2.86).